2018
DOI: 10.2196/11191
|View full text |Cite
|
Sign up to set email alerts
|

Enzalutamide Versus Abiraterone as a First-Line Endocrine Therapy for Castration-Resistant Prostate Cancer: Protocol for a Multicenter Randomized Phase 3 Trial

Abstract: BackgroundRecent large-scale randomized studies have demonstrated that 2 new hormone preparations (abiraterone and enzalutamide) prolong survival in docetaxel-treated or -naïve castration-resistant prostate cancer patients. However, no studies have directly compared antitumor effects between these 2 agents, and no clear guidelines are available for choosing between them.ObjectiveThe objective of this clinical study is to compare antitumor effects and adverse events between abiraterone and enzalutamide by alloc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…We also observed that many of the differentially methylated genes overlapped between Enzalutamide- and Abiraterone-treated patients. Although there are ongoing studies to compare efficacy of either treatment (55), the current consensus is that both perform similarly, and deciding between treatments in a patient-specific manner remains an ongoing challenge. We identified sets of genes altered in the promoter and gene body locations, including one large set amongst Enzalutamide treated patients.…”
Section: Discussionmentioning
confidence: 99%
“…We also observed that many of the differentially methylated genes overlapped between Enzalutamide- and Abiraterone-treated patients. Although there are ongoing studies to compare efficacy of either treatment (55), the current consensus is that both perform similarly, and deciding between treatments in a patient-specific manner remains an ongoing challenge. We identified sets of genes altered in the promoter and gene body locations, including one large set amongst Enzalutamide treated patients.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, there is no study directly comparing the efficacy of AA and ENZA in the first-line setting. There are still ongoing studies [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…However, to our knowledge, no head-to-head randomized, controlled trial has compared these two medications, except Khalaf and colleagues’ work which aimed at comparison of sequences of medications. Hara et al (2018) designed a study protocol for a multicenter, randomized, phase 3 trial to compare these two medications. The results of this trial are still pending.…”
Section: Introductionmentioning
confidence: 99%